2020
DOI: 10.1021/acsphotonics.0c00034
|View full text |Cite
|
Sign up to set email alerts
|

Size, Ligand, and Defect-Dependent Electron–Phonon Coupling in Chalcogenide and Perovskite Nanocrystals and Its Impact on Luminescence Line Widths

Abstract: The systematic study of electron−phonon coupling in nanocrystals (NC) via first-principles methods has been limited by the large system sizes presented by the NCs. Here, we present a method to extract electron−phonon coupling strengths from ab initio Molecular Dynamics simulations that is computationally less demanding. We use this method to investigate how electron−phonon coupling strengths depend on NC size, ligands, and defects for the model system of PbS NCs and also demonstrate its general applicability b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 60 publications
4
38
0
Order By: Relevance
“…These findings were reinforced by studies from Wood et al which showed that exciton coupling to localized vibrations arising from undercoordinated surface atoms broaden PL line widths, consistent with the observations that homogeneous PL line widths decrease with increasing QD size. 47 Phonons have also been noted to play a critical role in the emission of InP core/shell structures, with recombination processes involving both optical and acoustic phonons of the core and shell materials. 53 As the shell composition changes and allows for more electron wave function delocalization, slight polarization of the exciton occurs and the electron− phonon coupling is increased, resulting in decreased lifetimes observed via low-temperature TRPL spectroscopy.…”
Section: ■ Shellingmentioning
confidence: 99%
“…These findings were reinforced by studies from Wood et al which showed that exciton coupling to localized vibrations arising from undercoordinated surface atoms broaden PL line widths, consistent with the observations that homogeneous PL line widths decrease with increasing QD size. 47 Phonons have also been noted to play a critical role in the emission of InP core/shell structures, with recombination processes involving both optical and acoustic phonons of the core and shell materials. 53 As the shell composition changes and allows for more electron wave function delocalization, slight polarization of the exciton occurs and the electron− phonon coupling is increased, resulting in decreased lifetimes observed via low-temperature TRPL spectroscopy.…”
Section: ■ Shellingmentioning
confidence: 99%
“…[6,7] The structural flexibility of these materials results in various types extending from nanoplates (NPLs, 2D) [8] to nanowires (NWs, 1D), and even quantum dots (QDs, 0D). [9] CsPbX 3 QDs with controllable halide composition and tunable emission wavelength have already covered the full visible wavelength range. [10] Among the three typical CsPbX 3 NCs, green-emitting CsPbBr 3 QDs have been extensively studied as they show optical along with phase stability and a high PLQY of 60-80%.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent work has shown how the NC surface impacts electronphonon coupling strength and linewidth and recombination dynamics. [10,156] In summary, these examples from the PbS nanocrystal device space highlight the importance of control and characterization of nanocrystal surfaces. While the trend has been to think of nanocrystals as small particles of bulk, their large surface to volume ratios make the unique surface chemistry perhaps equally as important as the bulk.…”
Section: Packing and Ordering Of Nanocrystals Within Thin Filmsmentioning
confidence: 96%